1992
DOI: 10.1111/j.1600-0765.1992.tb01673.x
|View full text |Cite
|
Sign up to set email alerts
|

Volatile sulfur compounds in mouth air from clinically healthy subjects and patients with periodontal disease

Abstract: Volatile sulfur compounds (VSC) in mouth air were estimated by gas chromatography. The amount of VSC and the methyl mercaptan/hydrogen sulfide ratio were significantly increased in patients with periodontal disease. These two parameters also increased in proportion to the bleeding index and probing depth. A study was also done on the effect of removal of tongue coating on VSC concentrations in mouth air from patients with periodontal involvement. VSC and the methyl mercaptan/hydrogen sulfide ratio were reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
410
3
31

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 384 publications
(475 citation statements)
references
References 17 publications
31
410
3
31
Order By: Relevance
“…17 Previous studies indicated that increase in tongue coating and periodontal diseases were two major halitosis-inducing factors by creating areas allowing the overgrowth of anaerobic bacteria. [18][19][20] For this reason, in this study patients were instructed to brush both teeth and tongue.…”
Section: Discussionmentioning
confidence: 99%
“…17 Previous studies indicated that increase in tongue coating and periodontal diseases were two major halitosis-inducing factors by creating areas allowing the overgrowth of anaerobic bacteria. [18][19][20] For this reason, in this study patients were instructed to brush both teeth and tongue.…”
Section: Discussionmentioning
confidence: 99%
“…Volatile sulfur compounds are primarily produced through the putrefactive activity of bacteria present in saliva, in periodontal pockets, on the tongue surface, and in other areas (1,(3)(4)(5). In particular, the tongue dorsum has been implicated as a major cause for oral malodor (5).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of malodor comprises insufficient saliva flow, periodontal diseases, excessive microbial colonization of the tongue and poor oral hygiene (1)(2)(3). Malodorous volatile sulfur compounds originate from putrefactive activity of microorganisms in oral cavities, saliva, and periodontal pockets and on the tongue surface (1,4,5). Among the large number of bacterial species populating the oral cavity, Gram-negative anaerobic bacteria, including Porphyromonas spp., Veillonella spp., Prevotella spp., Fusobacterium spp., Tannerella forsythia, and Treponema denticola represent the microorganisms predominantly involved in VSC generation (6)(7)(8).…”
mentioning
confidence: 99%
“…[18][19][20][21][22] Ağız gargaralarının çoğunda bulunan kimyasal antimikrobiyal ajanlar VSB değerlerinde bir miktar azalma sağlasalar da 23 belirgin etki mekanik dil temizliği sonrasında sağlanmaktadır. 22,24 Sigara kullanımı kendine has yoğun kokusuyla ağız kokusu oluşturmakla birlikte 4 dolaylı olarak ağız ortamında meydana getirdikleri değişiklikler nedeniyle de halitozis oluşumunda etkilidir. Sigara içenlerde gingivitis ve periodontitisin daha şiddetli olduğu pek çok araştırıcı tarafından rapor edilmiştir.…”
Section: ----------------------------------------------------Gi̇ri̇şunclassified